Desarrollo en Centroamérica: hacia una agenda de políticas sociales. Análisis comparado entre el Triángulo Norte y Costa Rica - García Izarra, Luz; Miranda Delgado, Rafael Gustavo (CIICLA, Universidad de Costa Rica, 2020)
In Central America, especially since the 2000s, a broad set of social policies have been implemented. Therefore, the aim of the article is to compare the social policies of Costa Rica and the Northern Triangle: Guatemala, Honduras y El Salvador. The working hypothesis raises, from the perspective of political economy, that political institutions are the fundamental variable conditioning development, particularly social policies. The article shows that the early democratization of Costa Rica has allowed it to have a considerable tradition of social policies, which is presented as a fundamental variable to understand its relative success in reducing poverty compared to the countries of the Northern Triangle.